COLD WAR MUSEOLOGY - Douthwaite, Jessica HerausgeberIn; Nehring, Holger 1974- HerausgeberIn; Alberti, Samuel J. M. M. HerausgeberIn (ROUTLEDGE, 2025)
"Cold War Museology is the first volume to bring together interdisciplinary and international contributions from leading practitioners and academics specialising in Cold War museology. Bringing the most recent historiography of the Cold War into conversation with museological theory and practice, chapters within the volume analyse the current condition of Cold War museology. By unpicking some of the unique challenges facing museum specialists dealing with the Cold War, this book takes a lead in developing the collection, display and interpretation of this history. The chapters question what makes a Cold War object; address the complexity of Cold War time; face up to questions of Cold War race, gender and imperialism; and reveal how to materialise the Cold War imaginary in museums. Most importantly perhaps, the volume demonstrates that, a consideration of the interconnecting forces of global twentieth-century history enables experts to add important complexity and nuance to the narratives with which they work and improve visitor understandings through innovative interpretations. Cold War Museology will encourage readers towards a more nuanced, holistic and inclusive approach to Cold War materiality in museums. It will be of great interest to academics, museum professionals and students engaged in the study of museums, heritage and the Cold War, as well as those with an interest in archaeology, media, culture and memory"--